Study of Major Congenital Anomalies in Neonates born at Dhaka National Medical Institute Hospital - Karim, Rashidul; Uddin, Sultan; Rahman, Md Shafiqur; Sultana, Humayra; Rahat, Syeda Farzana (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Congenital malformations are major contributors of neonatal mortality or life long disability. Major malformation accounts for 15% of neonatal death. It is a priority health problem in newborn. The objective was to study opted to know the frequency, the pattern of congenital anomalies, associated risk factors, various system involved and immediate outcome of congenital malformations in newborns. Methods: This prospective hospital based observational study was carried out in the department of Paediatrics, Dhaka National Medical College and Hospital, Dhaka for a period of 3 years from 1st January, 2016 to 31st December, 2018. All congenital anomalous babies during the study period either detected before birth by ultrasonography of mother or detected at birth were included in this study. Diagnosis of congenital anomalies was based on clinical evaluation of newborn babies by the pediatrician and other appropriate investigations such as radiography, ultrasonography, echocardiography and chromosomal analysis etc. Results: The anomalies in this study were divided into major and minor anomaly. During the study period 68 newborns with major congenital anomalies were included. Major anomalies identified involved the gastro-intestinal (GE) system (30.87) was found to be the commonest type of anomaly. Cleft lip and cleft palate (14.70%) was the most common anomaly seen in the gastro-intestinal system. Of the 68 major anomalous babies, 8 (11.76%) babies had multiple anomalies. Out of 68 newborn, 26.47% were still births and 73.53% were live births. Among the anomalous babies 67.65% were male and 32.35% were female. Of them birth weight less than 2.5 kg were 39.71% and weighing 2.5 kg or more were 60.29%. Out of total 68 mothers with major congenital anomalous babies, 58.82% of multiparas, more than half of the mothers (76.47%) aged <35 years, 52.94% of babies delivered <37 weeks of gestational age were found. 23 (33.82%) mothers had history of significant maternal illness, history of previous abortion 29 (42.65%), gave the history of previous congenital anomalous babies (10.29%) and also 54.41% of mothers were the history of irregular/absent antenatal checkup. Conclusion: Congenital anomalies is a priority health problem in newborns. This study has highlighted the prevalence and types of congenital anomalies seen in our locality. Results of the study can be used to predict future incidence of anomalies and to increase public awareness about congenital anomalies to take preventive measures. J. Dhaka National Med. Coll. Hos. 2019; 25 (01): 06-10